Pengaruh Heat-Moisture Treatment dan Penambahan Natrium Tripolifosfat terhadap Kualitas Mi instan dari Pati Ubi Jalar (Ipomoea batatas (L) Lam) - Chatarina Lilis Suryani (Universitas Atma Jaya Yogyakarta, 2006)
The objective of the present study was to evaluate the effect of heat-moisturetreatment (HMT) and sodium tripolyphosphate (STPP) addition on the quality ofinstant noodles from sweet potato starch. The diversification of raw material used innoodle production often necessitates processing modifications. Heat-moisturetreatment was applied to native sweet potato starch (HMTSPS) in three conditions(1100C; 10, 20 and 30 min) and STPP was added in three level (0,60; 0,75 and 0,90%).HMTSPS, STPP, water, lecitin and CMC were mixed. The mixture was pelleted,steamed and extruded. The extruded noodles were dried using a microwave oven. Thenoodles were evaluated both when dry and after cooking. The HMT method andSTPP addition improved noodle quality. Swelling index, solid loss and cooking loss ofthe noodles was decreased, while the texture and the elastisity of the noodles washigher. But noodles made with added of STTP more than 0,75% had low elastisity.The best instant noodle prepared by HMT method for 20 min and added of STTP0,75%.